The Use of Memrise Application to Improve Students’ Vocabulary Mastery in The Class VII at Junior High School - Mona Zumara Attaiya; Zuhri Efendi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to probe the effectiveness of the Memrise operation in perfecting vocabulary mastery among seventh- grade students at SMPN 2 Susoh. exercising a quantitative approach with a quasi-experimental design, the exploration involved two groups an experimental group comprising 26 students who entered vocabulary instruction using Memrise, and a control group of 28 students who were tutored through conventional styles. Data were collected through pre-tests and post-tests conforming of 20 multiple- choice particulars designed to assess students’ vocabulary mastery ahead and after the treatment. The results of the independent samples t- test revealed a statistically significant difference between the post-test scores of the two groups, with the experimental group achieving a advanced mean score 85.00 compared to the control group 66.61, and a significance value of p = 0.000( p< 0.05). These findings indicate that the Memrise operation has a substantial positive impact on students’ vocabulary accession. The study suggests that integrating mobile- assisted language literacy (Boardwalk) tools similar as Memrise can enhance students’ provocation, engagement, and retention in vocabulary literacy. Its interactive and tone- paced literacy features make it a precious pedagogical tool for English language instruction, particularly in secondary education. preceptors are encouraged to borrow technology- grounded media to support effective vocabulary development in the classroom.